Clinical case of tuberculous pleurisy in sarcoidosis patient - O.D. Nikolaeva (Civic Union "Communicable Diseases Intensive Care Association", 2022)
In recent years, there has been an increase in cases of sarcoidosis in our country. Cases of a combination of tuberculosis and sarcoidosis are observed. A clinical case of the development of tuberculous pleurisy in patients with pulmonary sarcoidosis, who had previously received courses of glucocorticosteroid therapy, is presented. The tuberculous etiology of pleurisy was established by microbiological detection of the pathogen in the exudate and biopsy and histological examination.